Hambatan Penyerahan PSU Perumahan: Menilik Melalui Model Implementasi Kebijakan Ade Kearns & Louise Lowson di Kabupaten Sidoarjo - Ramadhon, Achmad Idris (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
The number of housing units with the handover of residential Prasarana, Sarana, dan Utilitas (PSU) by developers in Sidoarjo Regency is inversely proportional. As of 2023, there were 535 housing units, and 25 Surat Keterangan Rencana Kota (SKRK) were issued in 2024, whereas the number of Berita Acara Serah Terima (BAST) for the handover of residential PSU until September 2025 was only 128. However, the handover of residential PSU to the Regional Government is a mandatory obligation for every developer. This research focuses on the implementation of Sidoarjo Regent Regulation Number 53 of 2024 concerning Procedures for the Handover and Utilization of Residential PSU. The purpose of this research is to examine the extent of implementation of this regulation. This study uses a qualitative method with a case study approach. The results show that the implementation of Sidoarjo Regent Regulation Number 53 of 2024 has been running well, with a focus on improving Human Resources and inter-agency communication.